A Study of Spirituality at Work of Professional Nurses - Sakthong, Ubonrat; Prachusilpa, Gunyadar (Journal of The Royal Thai Army Nurses, 2022)
This descriptive research aimed to study spirituality at work of professional nurses. The Delphi technique was used in this study. Participants were 20 experts comprising 1) administrators from the Human Resources Department 2) nursing administrators 3) administrators from the Thailand Nursing and Midwifery Council 4) academics/nursing instructors 5) nurses at practitioner level. The Delphi technique consisted of three steps. Step one: all of experts were asked to spirituality at work of professional nurses. Step two: the data were analyzed by using content analysis to develop a rating scale questionnaire. All items in the questionnaire were ranked by level of the spirituality at work of professional nurses. Step three: items were analyzed by using median and interquartile range to develop a new version of the questionnaire. The new questionnaire was sent to previous experts for confirmation. Ranked items were analyzed by using median and interquartile range again to summarize the research. The results of this research showed that the spirituality at work of professional nurses consisted of 3 components as follows: 1) Self understanding consisted of 12 items. 2) Inner motivations consisted of 12 items 3) Positive attitude towards the work consisted of 16 items.